COMPARING ELT POLICIES IN JAPAN AND SOUTH KOREA: DO THEY STILL NEED ENGLISH? (A LITERATURE STUDY) - Abd Rajab (Education and Talent Development Center Indonesia (ETDC Indonesia), 2021)
Language policy is one issue that should be highlighted because language policy is one of the most important things to develop in a country. In language, the main goal to be achieved is the successful delivery of our goals and objectives to the listener. Thus, Language policy is concerned with a highly complex issue; therefore, language policy as a separate field of study requires an interdisciplinary approach drawing upon the knowledge and tools of several academic disciplines such as applied linguistics, sociolinguistics, sociology, anthropology, and political theory. This paper aimed to suggest for Indonesia English Education based Japan and South Korea practice in ELT.